Evaluation of the CO2 Poisoning Effect on a Highly Active Cathode SrSc0.175Nb0.025Co0.8O3-δ in the Oxygen Reduction Reaction - Zhang, Y.; Yang, G.; Chen, G.; Ran, R.; Zhou, W.; Shao, Zongping (2016)
A solid oxide fuel cell (SOFC) is a highly efficient device for converting chemical energy to electrical energy. In addition to the efforts to reduce the operating temperature of SOFCs to below 600 °C, research studies of the basic mechanism of CO2 poisoning on cathode materials are envisioned to improve the operation of dual-chamber SOFCs using ambient air. In this work, we comparatively studied the CO2 poisoning effect on two highly active perovskites SrSc0.175Nb0.025Co0.8O3-δ (SSNC) and Ba0.5Sr0.5Co0.8Fe0.2O3-δ (BSCF), using complementary characterization techniques, e.g., powder X-ray diffraction (XRD), Fourier transform-infrared (FT-IR) spectroscopy, atomic force microscopy (AFM), scanning electron microscopy (SEM), CO2-temperature-programmed desorption (CO2-TPD), and electrochemical impedance spectroscopy (EIS). The SSNC cathode shows better tolerance to CO2 as compared with BSCF, which is attributed to the absence of Ba, higher average metal–oxygen bond energy (ABE) of SSNC, and the higher acidity of Nb5+ cations, whereas the oxygen vacancy concentration plays a less important role.